Teaching controversial issues in RE: the case of ritual circumcision - Lippe, Marie von der (British Journal of religious education, 2021)
What are controversial issues? Who decides whether something is controversial, and how does it affect how a subject is taught whether a topic is presented as either controversial or not so? Although there has long been a lively debate within educational research on what criteria should be used to determine whether or not an issue is controversial, this topic has been less discussed in the specific context of religious education. At the same time, recent classroom studies has uncovered a finding that teachers of religious education feel that it is demanding to address controversial issues in their teaching, and that they lack the basic disciplinary and didactic skills to manage issues of such complexity. The main aim of this article is to bring the discussion about teaching controversial issues into the scholarly field of religious education and to explore the issues in deciding whether a topic should be considered controversial or not, and whether it should be taught as an open or a settled question.